Effectiveness of Good Customer Service Satisfaction in the 21st Century Business Relations - Amos Ojo Adedeji, Ph.D (Citakonsultindo, 2025)
Customer is a boss, regardless of whether his work is a menial job or is in charge of the largest company in the world. In recent years, marketing has become the bedrock of business, equally customer satisfaction has grown in importance in any commercial organisation. The study interrogate the effectiveness of good customer service satisfaction in the modern day business dealings. It is qualitative in nature relying mainly on secondary source of data collection and analysis. The work found customer loyalty, positive relationship cum increased profit, higher inventory turnover of the organisation, personal satisfaction and fulfillment of customers, and better and higher morale of employee as the effect of good customer service. Conversely, customer service satisfaction are been defied by a numbers of barriers, namely overworked staff, non-caring culture, poor communication value, lack of adequate training, and superior-subordinate relationship. The study concluded by recommending